IMPACT OF CELOSIA ARGENTEA VAR. CRISTATA(COCKSCOMB) EXTRACT ON COLOR ENHANCEMENT IN FISH; PUNTIUS CONCHONIUS. - SANNA BASHIR,; ANAYITULLAH CHESTI,; MANSOOR RATHER,; MASOOD UL HASSAN BALKHI,; SUMIRA JAN AND MAHIN MUNEER., (The Bioscan, 2021)
The 60-day trial was performed to evaluate the impact of Celosia argentea var. cristata flower extract in enhancing and maintaining natural pigmentation in Rosy barb, Puntius conchonius. The extract was incorporated at the rate of 0% (Control), 0.5% (T 1 ), 1.0 %(T 2 ) and 1.5% (T 3 ) with basal feed (protein 32%) and fed to the fish weighing 0.45 g to 0.49 g initially. It was observed that the muscle pigmentation increased with increasing cockscomb extract with 1.5% extract level fed group showing the highest carotenoid content followed by 1.0% and 0.5 % extract levels which were significantly higher (p<0.05) than that of the control group (0%). The carotenoid retention rate in the muscle was also found to be significantly higher (9.5%± 0.125) at 1.5% as compared to 1.0% (7.2%± 0.09) and 0.5% (4.95% ± 0.09) extract levels. No significant change was observed in the physico- chemical parameters of water. The study concluded that locally available Celosia argentea flowers can be used to formulate the natural color enhancing diets for less commercially valuable fish, Rosy barb, Puntius conchonius at 1.5% level